1999
DOI: 10.1046/j.1365-2265.1999.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of oestrogen in male sexual behaviour: insights from the natural model of aromatase deficiency

Abstract: The study of the sexual behaviour in this man with aromatase deficiency suggests that oestrogens in humans do not affect gender-identity and sexual orientation but could have a role in male sexual activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 50 publications
0
68
0
2
Order By: Relevance
“…This suggests that oestrogens could have a role in supporting libido. 10 Letrozole was used in this study because indirect comparisons between letrozole and anastrozole suggest stronger evidence for the benefits of the use of letrozole in breast cancer treatment in postmenopausal women who require oestrogen-deprivation therapy. This is probably due to its stronger inhibition of aromatase.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that oestrogens could have a role in supporting libido. 10 Letrozole was used in this study because indirect comparisons between letrozole and anastrozole suggest stronger evidence for the benefits of the use of letrozole in breast cancer treatment in postmenopausal women who require oestrogen-deprivation therapy. This is probably due to its stronger inhibition of aromatase.…”
Section: Discussionmentioning
confidence: 99%
“…Again, the congenital lack of estrogens during infancy and puberty could compromise the integrity of the HPG axis as a consequence of chronic severe estrogen deprivation. It should be remarked that congenital estrogen deficiency implies a severe estrogen depletion also during fetal life, thus, early development and maturation of the hypothalamus may be compromised (45) as well as the masculinization of hypothalamus, a process that involves GnRH neurons (45,46) and hypothalamic structures (47,48). Recently, a pivotal role of estradiol in HPG and pituitary maturation has been postulated in rodents (40,49).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, six of our letrozole-treated patients reported a loss of libido, despite the supraphysiological levels of T, and confirmed that oestrogens could play a role in supporting libido. 15 The following considerations compelled us to study the NOA patients who yielded no spermatozoa following FNA. Despite the availability of ultrasound and biochemical techniques to differentiate NOA patients from obstructive azoospermia patients, [16][17][18] FNA has been regarded as a highly informative and minimally invasive method.…”
Section: Letrozole For Azoospermia and Cryptozoospermia G Cavallini Ementioning
confidence: 99%